EFEKTIVITAS KONSUMSI DAUN SEREH DAN JAHE DALAM MENGATASI MORNING SICKNESS PADA IBU HAMIL TRIMESTER SATU DI KLINIK BIDAN MARIANA KABUPATEN PADANG LAWAS UTARA TAHUN 2020 - Pratiwi Nasution; Nur Khadijah Daulay (Jurnal Maternitas Kebidanan, 2023)
Morning Sickness in first trimester pregnant women is still a problem, because many mothers face it with anxiety and discomfort. In fact, many pregnant women have to take drugs or other alternative measures to deal with nausea and vomiting which are not good for the health of the womb. Purpose : To determine the Effectiveness of Lemongrass Leaves and Ginger in Overcoming Morning Sickness in First Trimester Pregnant Women at Mariana Am.Keb Clinic in Ubar Village, Padang Bolak Julu District, North Padang Lawas Regency in 2020. Method : a Quasi Experiment with a one group pretest and post test without control design. The sample of this study was 22 pregnant women in the first trimester who experienced physiological nausea and vomiting. Results : Obtained using the Paired Sample T test, the P-Value (Sig 2-tailed) was (0.000) which was smaller than the value of (.05), so it was concluded that Ho was rejected and Ha was accepted. Conclusion : There is Effectiveness of Consumption of Lemongrass Leaves and Ginger in Overcoming Morning Sickness in first trimester Pregnant Women at Mariana Am.Keb Clinic in Ubar Village, Padang Bolak Julu District of North Padang Lawas Regency